Peritoneal Dialysis with Marked Pneumoperitoneum - Norio Nakamura; Masamichi Nakata; Daiki Nagawa; Ikuyo Narita; Takeshi Fujita; Reiichi Murakami; Michiko Shimada; Hirofumi Tomita (Case Reports in Nephrology)
Pneumoperitoneum, the presence of free air within the peritoneal cavity, is often caused by the perforation of gas-containing viscus and commonly requires surgical treatment. However, in patients with peritoneal dialysis, free air is commonly seen on X-ray. We present the case of a patient with peritoneal dialysis with marked pneumoperitoneum. A 75-year-old Japanese male with end-stage renal disease due to antineutrophil cytoplasmic antigen-associated vasculitis had been receiving continuous ambulatory peritoneal dialysis for 9 years. He had a poor appetite and general malaise without abdominal pain or fever. These symptoms gradually worsened, and he was hospitalized. At the time of admission, chest X-ray revealed bilateral free air in the abdomen. Subsequent computed tomography of the abdomen revealed marked pneumoperitoneum. Peritonitis due to perforation of the digestive tract was considered; however, the absence of abdominal pain, fever, and turbidity of dialysis drainage indicated that peritonitis was unlikely. Insufficient air venting during continuous ambulatory peritoneal dialysis bag replacement was suspected. The bag was carefully changed, resulting in a gradual decrease in the free air. We encountered a patient with continuous ambulatory peritoneal dialysis who had significant free air in the abdominal cavity in the absence of peritonitis. The source of the air was determined to be the dialysis bag due to insufficient venting during replacement. This case underscores the importance of instructing patients with continuous ambulatory peritoneal dialysis on the thorough removal of air from the bag during replacement.